Unemployment insurance reform – 1991–2006 : a new balance between rights and obligations in France, Germany, Portugal and Spain - Arcanjo, Manuela (2014)
The purpose of this article is twofold. First, focusing on unemployment insurance schemes, the article seeks to identify the development of social rights and obligations in four countries (France, Germany, Portugal and Spain), representative of the conservative regime, over the period 1991–2006. Second, the article aims to verify whether or not there was a common reform trajectory in time as well as in space, given the already known divergence over the appropriateness of classifying Mediterranean countries within the framework of a specific regime. Based on analysis of 25 legislative changes concerning entitlement and eligibility criteria, the study presents three major findings. First, the four insurance schemes reveal a new balance between (weaker) social rights and (stronger) obligations, which may indicate a trend toward a re-commodification of work. Second, Portugal adopted a specific trajectory while the Spanish reform process more closely resembled that carried out by France and Germany. Finally, two waves of reform may be identified: first, between 1991 and 1997 and justified by cost-containment concerns and, subsequently, from 2001 onwards, associated with a stronger recalibration of benefit rights.